[PP.20.18] DETERMINANTS OF CAROTID ATHROSCLEROSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2017) - Anyfanti, P.; Triantafyllou, A.; Koletsos, N.; Mantzouranis, E.; Triantafyllou, G.; Chatzimichailidou, S.; Gkaliagkousi, E.; Aslanidis, S.; Douma, S.
Abstract : Objective: Cardiovascular risk factors are of profound importance for the development of atherosclerosis. However, it remains unclear whether they exert the same impact on patients with chronic inflammatory background, as is the case in rheumatoid arthritis (RA) patients, compared to hemodynamic or disease-related parameters. Design and method: Consecutive RA patients attending our Rheumatology Outpatient Unit were assessed for carotid atherosclerosis by estimating carotid intima-media thickness (cIMT) using ultrasound (ALOKA e-tracking software). Impedance cardiography (ICG) was used to evaluate hemodynamic parameters, including systemic vascular resistance index (SVRI); stroke index (SI); cardiac index (CI), and thoracic fluid content index (TFCI). Disease activity was assessed by the treating rheumatologist using the Disease Activity Score in 28 joints (DAS28). The Health Assessment Questionnaire Disability Index (HAQ-DI) and the HAQ Pain Visual Analogue Scale (VAS) were completed to evaluate physical function and arthritis-related pain, respectively. Inflammatory markers and lipid fractions were measured in blood samples. Results: Among 92 RA patients aged 61.9 ± 11.5 years (females: 79.3%), cIMT was 0.69 ± 0.13 mm and correlated with age (r = 0.610, p < 0.001), systolic blood pressure (r = 0.277, p = 0.008) and body mass index (r = 0.312, p = 0.003). Males exhibited higher cIMT compared to females (0.76 ± 0.15 vs 0.68 ± 0.11 mm, p = 0.012), and the same was observed for diabetic compared to non-diabetic patients (0.78 ± 0.17 vs 0.69 ± 0.12 mm, p = 0.044). A significant association was found between cIMT and erythrocyte sedimentation rate (r = 0.037, p = 0.037), as well as triglycerides (r = 0.289, p = 0.009), but not with other lipid fractions. Regarding disease-related factors, cIMT correlated with HAQ-DI (r = 0.299, p = 0.010) and HAQ-VAS pain (r = 0.312, p = 0.010) scores but not with disease duration or DAS28. Of the ICG-derived hemodynamic parameters, cIMT significantly correlated with SVRI (r = 0.343, p = 0.001) and CI (r = –0.244, p = 0.020). After adjusting for anthropometric, hemodynamic and inflammatory factors in the linear regression analysis, age (p < 0.001), sex (p = 0.029) and diabetes mellitus (p = 0.024) remained independent predictors of cIMT in our population. Conclusions: Although several anthropometric, hemodynamic and inflammatory parameters may be implicated in the development of carotid atherosclerosis, factors associated with an unfavorable cardiovascular risk profile remain major predictors of impaired cIMT, especially in relatively well-controlled patients with RA treated on an outpatient basis.